(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Mr. Wilberforce Kasangaki, PG Scholar, Department of Regulatory Affairs, Ramanbhai Patel College of Pharmacy, CHARUSAT, Changa, Gujarat, India Abstract Pharmaceutical manufacturing encompasses both sterile and non-sterile preparation techniques required for specialized medication production beyond commercial availability. Non-sterile compounding transforms raw ingredients into patient-specific formulations including capsules, suspensions, ointments, and suppositories using pharmaceutical calculations ensuring accurate concentration, beyond-use dating based on stability data, and proper documentation meeting regulatory requirements including USP <795> standards and DQSA provisions. Sterile compounding applies aseptic techniques to prepare injections, ophthalmics, and other contamination-sensitive products, following USP <797> classifications of risk levels, environmental monitoring requirements, personnel qualification procedures, and beyond-use dating limitations that prevent microbiological or particulate contamination. Equipment and techniques for pharmaceutical preparation include electronic balances, ointment mills, powder blenders, laminar airflow workbenches, biological safety cabinets, and automated compounding devices, each requiring specific operation protocols, maintenance procedures, and performance verification to ensure accurate, consistent product generation. Quality assurance programs integrate environmental monitoring, personnel training, process validation, finished product testing, and comprehensive documentation systems that verify preparation integrity through particulate analysis, sterility testing, endotoxin evaluation, and potency assessment when applicable. These manufacturing principles enable pharmacies to face unmet medication needs through standardized processes that maintain product integrity, ensure patient safety, and fulfill regulatory obligations while providing therapy options unavailable through commercial channels Keywords: Aseptic technique; Beyond-use dating; Environmental controls; Preparation validation; Regulatory compliance VIEW PDF